Immunological characterization of the aryl hydrocarbon receptor (AHR) knockout rat in the presence and absence of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD). (10th August 2016) - Phadnis-Moghe, Ashwini S.; Chen, Weimin; Li, Jinpeng; Crawford, Robert B.; Bach, Anthony; D'Ingillo, Shawna; Kovalova, Natalia; Suarez-Martinez, Jose E.; Kaplan, Barbara L.F.; Harrill, Joshua A.; Budinsky, Robert; Rowlands, J. Craig; et al.
Abstract: The aryl hydrocarbon receptor (AHR) has been extensively characterized for the essential role it plays in mediating the toxic responses elicited by 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD). Despite similarities across animal species, species-specific differences exist in the profile of toxicity and sensitivity to TCDD owing, in part, to differences in the AHR. Newer reports have implicated the importance of AHR in the development and regulation of the immune system. Our present studies seek to further explore the essential role of AHR in lymphoid tissue composition, B cell function and the immunological responses after TCDD administration using the recently established AHR KO rats. Comprehensive immune cell phenotyping showed a decrease in the CD8 + T cell, CD11c + populations and an increase in NKT cells in 3-week-old AHR KO rats compared to the WT controls. The lipopolysaccharide-induced IgM response and proliferation was markedly suppressed in the WT but not in the AHR KO B cells in the presence of TCDD. However, the percentage of LPS-activated IgM + B cells was significantly higher in the AHR KO B cells as compared to that of WT suggesting the role of AHR in regulating the IgM response. The use of an AHR antagonist further alluded to the endogenous role of AHR in regulating B cell responses in the rat. Overall, the studies report for the first time, comprehensive immune cell phenotyping of the AHR KO rat and the endogenous role of AHR in the regulation of B cell function in the rat.